2018
DOI: 10.1049/iet-pel.2018.5338
|View full text |Cite
|
Sign up to set email alerts
|

Direct grid‐side current model predictive control for grid‐connected inverter with LCL filter

Abstract: On control of the grid-connected inverter (GCI) with LCL filter, the inverter-side current model predictive control is adopted conventionally. The ultimate grid-side current is controlled indirectly by control of inverter-side current. The ideal scenario is that grid-side current is directly controlled. However, the conventional control model is complicated and the calculation is heavy. This study proposed a novel direct grid-side current model predictive control (GSC-MPC) for GCI with LCL filter. Based on tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Thus, we only have predefined passive components of the LCL filter and in the case of acceptable tolerance (10%-20%) we do need any identification. Many research papers have addressed the grid-connected systems [34][35][36][37][38][39]. At the same time, none of them address no-load or idle operation of the inverter.…”
Section: Indirect Model Predictive Control Proposed For Voltage Sourcmentioning
confidence: 99%
“…Thus, we only have predefined passive components of the LCL filter and in the case of acceptable tolerance (10%-20%) we do need any identification. Many research papers have addressed the grid-connected systems [34][35][36][37][38][39]. At the same time, none of them address no-load or idle operation of the inverter.…”
Section: Indirect Model Predictive Control Proposed For Voltage Sourcmentioning
confidence: 99%
“…Singleinductance filters, which are of large volume and weight, not only cost a lot but also significantly increase the loss. Given the problems, single-inductance filters are usually replaced with LCL filters in high-power inverters [2]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Its uniqueness include the time-domain approach, predictive nature, and cost-function-based control feature. Two basic variants of MPC with active-damping consideration have been reported to date: finite-control-set (FCS) MPC [25]- [29] and continuous-control-set (CCS) MPC [30]. Authors in [25]- [28] have investigated the possibilities of appending the virtual resistance based active damping techniques to FCS-MPC.…”
Section: Introductionmentioning
confidence: 99%
“…FCS-MPC schemes with two prediction horizons that simultaneously control three-vector-variables (i.e. complex variables) consisting the converter current vector, grid current vector, and capacitor voltage vectors, are proposed in [27], [29]. On the other hand, [28] showed that a twovector-variables cost function can readily provide active damping without virtual-resistance method, and that the converter switching frequency can be directly manipulated through a weighted cost function.…”
Section: Introductionmentioning
confidence: 99%